Aflatoxin contamination of milk marketed in Pakistan: A longitudinal study - Yunus, Agha Waqar; Imtiaz, Nida; Khan, Haider; Ibrahim, Mohamed N.M.; Zafar, Yusuf (MDPI, 2019)
A longitudinal one-year study was conducted to determine aflatoxin M1 levels in different types of milk marketed in Pakistan. Processed and raw liquid milk from 21 sources, two milk powder and six tea whitener brands were sampled on monthly basis from Islamabad. The aflatoxin M1 levels in liquid milk were lower (p < 0.05) in summer (April to July) compared with the levels in winter (January, November and December). The mean aflatoxin M1 levels were 254.9, 939.5, and 1535.0 ng/L in UHT, pasteurized, and raw milk, respectively (differing at p < 0.001). The mean toxin level in powdered milk after reconstitution was 522.1 ng/L. Overall, 12.9, 41.0, 91.9 and 50.0% of the UHT, pasteurized, raw and powdered milk samples, respectively, exceeded the Codex maximum tolerable limit of 500 ng of aflatoxin M1/L. It was estimated that consumers of raw and processed milk were exposed to 11.9 and 4.5 ng aflatoxin M1, respectively, per kg of body weight daily. The study indicates potential aflatoxin M1 exposure risks for the consumers of raw milk in the country. The levels of the toxin though comparatively lower in milk powder, requires attention as this type of milk is consumed by infants.